An investigation into the effect of a staffing strategy on patient care in a selected hospital in Kwazulu-Natal - McIntosh, Jane (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MCur (Interdisciplinary Health Sciences. Nursing Science))--University of Stellenbosch, 2008.